Effects of different organic manure on growth, yield and quality of garden egg (Solanum melongena) in Ondo State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
A field experiment was conducted at the Teaching and Research Farm of the Federal University of Technology, Akure, Ondo State, Nigeria, in the early cropping season of 2016 to examine effects of manure types and rates of application on soil properties, growth, yield and quality of garden eggs (Solanum melongena). The experiment was laid out in a randomized complete block design (RCBD), with three replications. Poultry manure, compost, sunshine manure, fertiplus and cow dung were the selected manures. Soil samples were also collected before planting and at harvest forphisico-chemical analysis. The growth parameters assessed were: plant height (cm), stem girth (mm), number of branches per plant, and number of leaves per plant; while the yield parameters were number of fruits per plant, weight of fruits and proximate composition of fruits. Results from the study showed that application of manure had positive effects on growth of Solanum melongena, yield and quality. Cow dung had higher fruit yield at maturity weighing 2773.92/g.  The proximate composition of the garden egg showed that the percentage ash, crude protein, crude fibre, fats and moisture contents differed significantly (p < 0.05) across treatments.  The highest percentages of moisture content and crude protein were in garden eggs in plots treated with cow dung. Solanum melongena in plots treated with poultry manure had the highest percentage of ash while Solanum melongena in plots treated with sunshine manure had the highest percentage of fat. The results revealed cow dung as the most effective at improving growth and yield of Solanum melongena
Keywords: Manure; Garden egg; Growth; Physico-chemical; Yield